Hybrid Inorganic-Organic Inverted Solar Cells with ZnO/ZnMgO Barrier Layer and Effective Organic Active Layer for Low Leakage Current, Enhanced Efficiency, and Reliability - Dikshit A.K.; Maity S.; Mukherjee N.; Chakrabarti P. (My University, 2025)
This article reports fabrication and characterization of an Inverted inorganic-organic hybrid solar cell based on ITO/(ZnO/ZnMgO)/ZnONR/PCBM/P3HT:PCBM/PEDOT:PSS/Ca-Al heterostructure. Four different cells were fabricated with and without the presence of both the ZnO/ZnMgO barrier layer and ZnO nanorod (NR) structures. The oxide layers were grown on indium tin oxide (ITO) coated glass substrates through the following approaches: i) ZnO layer by radio frequency (RF) sputtering, ii) ZnMgO layer by pulsed laser deposition technique, and iii) ZnO NR by hydrothermal method. Compared to conventional only ZnO based solar cells, incorporation of ZnO/ZnMgO layer as the barrier layer resulted in low leakage current that enormously improved the cell performance. The binary metal oxide layer offers a chemical barrier that protects the ITO layer and leads to better electron collection. Incorporation of a thick (∼300 nm) P3HT:PCBM layer (instead of conventional and thin (∼100 nm) P3HT coating) between the ZnO/ZnMgO and PEDOT:PSS layers improves electron collection efficiencies. Improvement in short circuit current density (JSC) was observed from 9.5 to 12.3 mA/cm2. A significant increase in external quantum efficiency was also observed. Both JSC and fill factor were found to be improved simultaneously owing to suitable shunt and series resistance attributes. Furthermore, the presence of the thin ZnMgO layer between P3HT:PCBM and dense ZnO layer suppresses the impact of oxygen vacancies, which in turn improves the charge carrier mobility and lowers leakage current. The fabricated cell showed a power conversion efficiency of ∼4.95%. Reliability study for 1400 h indicates that the device outperforms the conventional ZnO-based inverted organic solar cells. © 2011-2012 IEEE.